2023
DOI: 10.1186/s12911-023-02147-x
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing the usability, acceptability, and future implementation of the Whole Day Matters Tool and User Guide for primary care providers using think-aloud, near-live, and interview procedures

Abstract: Background Canada’s 24-Hour Movement Guidelines for Adults have shifted the focus from considering movement behaviours (i.e., physical activity, sedentary behaviour, and sleep) separately to a 24-h paradigm, which considers how they are integrated. Accordingly, primary care providers (PCPs) have the opportunity to improve their practice to promote all movement behaviours cohesively. However, PCPs have faced barriers to discussing physical activity alone (e.g., time, competing priorities, inadeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Transcripts and behavioral analyses from these sessions showed where, when, and how providers accessed the support tool to efficiently provide the necessary services; they also revealed workflows that conventional think-aloud testing never caught. Morgan and colleagues [4] assessed the usability of a patient-care guide by coupling think-aloud testing with mock patient discussions. Post hoc interviews and transcript content analyses showed that accessing the guide in "practice" was hindered by several obstacles.…”
Section: Remote Observations Through Conversation Analysismentioning
confidence: 99%
“…Transcripts and behavioral analyses from these sessions showed where, when, and how providers accessed the support tool to efficiently provide the necessary services; they also revealed workflows that conventional think-aloud testing never caught. Morgan and colleagues [4] assessed the usability of a patient-care guide by coupling think-aloud testing with mock patient discussions. Post hoc interviews and transcript content analyses showed that accessing the guide in "practice" was hindered by several obstacles.…”
Section: Remote Observations Through Conversation Analysismentioning
confidence: 99%